THE ART OF WRITING AN ESSAY - Matqurbonova Ro’zaxon Zokirjon qizi (TADQIQOTLAR, 2025)
Abstract: Essay writing is a crucial skill that combines creativity, critical thinking, and structured expression. Mastering this art involves understanding the key components such as clarity, coherence, and argumentation. This article explores the essential elements of essay writing, emphasizing the importance of planning, organization, and revision in producing a compelling piece. By focusing on effective techniques, writers can develop their skills and create essays that effectively communicate their ideas.